(untitled) (Empower : Jurnal Pengembangan Masyarakat Islam, 2026)
This research is motivated by environmental degradation caused by sedimentation, urbanization, and poor drainage systems in areas along the Tjimanoek River in Indramayu. Therefore, this study aims to determine how the process of empowering riverbank communities is implemented in the Tjimanoek Indramayu riverbank ecology program. The method used is a qualitative descriptive approach, with data collection techniques including interviews, observations, and documentation studies. Interviews were conducted using purposive sampling with the snowball technique, data validation through triangulation, and analysis following the stages of Miles and Huberman: data reduction, data presentation, and data verification. The results of this study involve the collaboration of Penta Helix, namely the government, universities, industry, communities, and the media. This program uses an Ecocriparian approach, which emphasizes the restoration of natural river functions, reduction of domestic pollution, environmental education, and ecotourism. The results show that the community empowerment process in Tjimanoek Park began with government planning, specifically by the Department of Housing and Settlement, together with the Polytama company. Then, after planning, program implementation involves the Penta Helix, including employees from Kimrum, companies, society or communities, mass media, and universities.